Effect of wave shift of porous slab on thermo-hydraulic transport characteristics of laminar flow through a wavy channel. (2022) - Kumar, Prince; Pandey, K.M.
Abstract: In the present numerical study, the finite element method is adopted to investigate the thermo-hydraulic transport characteristics of two-dimensional, steady, Laminar flow of Newtonian fluid through partially porous wavy channel. The wavy channel consists a porous wavy slab at the center. Water is taken as working fluid with Prandtl number Pr = 6.93 and Reynolds number Re = 700 considered for all simulations. Results are investigated in the form of average Nusselt number (Nuavg ), Enhancement ratio (ER), Pressure drop ( Δ p ), Pressure ratio (PR), and Performance factor (PF) for different wave amplitudes ( α =0.06, 0.12, and 0.18) and wave phase shifts (φ = 0 0, 45°, 90° and 180°) of porous slab at different Darcy numbers range (Da = 10 -6 to 10 -2 ). Results reveal a significant increment in average Nusselt number with decreasing in Darcy number on the pressure drop penalty. The maximum value of ER found for geometry configuration α = 0.18 and φ = 90 0 at Darcy number Da = 10 -6, and on the other end, maximum PF is obtained at Darcy number Da = 10 -2 irrespective of geometry configurations. The lower value of ER was obtained at φ = 180 0 irrespective of wave amplitude and Darcy number. There is a significantly less effect of porous slab wave phase shift of φ = 45 0 and φ = 90 0 for given Da on PR at fixed wave amplitude.